1980
DOI: 10.1111/j.1540-6261.1980.tb03512.x
|View full text |Cite
|
Sign up to set email alerts
|

Affiliated Bank Performance and the Simultaneity of Financial Decision‐Making

Abstract: The remarkable growth of bank holding companies (BHCs) during the last decade has aroused a great deal of interest and controversy among academic economists and bank regulators. One of the important issues discussed has been the impact of holding company affiliation on the operating performance of the acquired banks. Subsequent empirical testing of the question has produced a wide array of results. Nevertheless, a recent survey of the literature by the staff of the Federal Reserve Board [18] concluded that whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The bank studies utilized several univariate [17,18,28,291 and multivariate tests [9,14,16,19,301 to examine financial and operating ratios. Most profitability studies cited found no significant tendency toward higher profit or higher growth rates for merged banks and BHCs.…”
Section: Neebmentioning
confidence: 99%
See 2 more Smart Citations
“…The bank studies utilized several univariate [17,18,28,291 and multivariate tests [9,14,16,19,301 to examine financial and operating ratios. Most profitability studies cited found no significant tendency toward higher profit or higher growth rates for merged banks and BHCs.…”
Section: Neebmentioning
confidence: 99%
“…Loan portfolio composition also differs between merged and independent banks. Merged banks have a larger proportion of business loans [ 14,26,281 (although another study indicates the reverse [19]). Real estate loans [19,26,281 are used more extensively by merging banks.…”
Section: Neebmentioning
confidence: 99%
See 1 more Smart Citation